2021
DOI: 10.2196/22909
|View full text |Cite
|
Sign up to set email alerts
|

Digital Natives’ Preferences on Mobile Artificial Intelligence Apps for Skin Cancer Diagnostics: Survey Study

Abstract: Background Artificial intelligence (AI) has shown potential to improve diagnostics of various diseases, especially for early detection of skin cancer. Studies have yet to investigate the clear application of AI technology in clinical practice or determine the added value for younger user groups. Translation of AI-based diagnostic tools can only be successful if they are accepted by potential users. Young adults as digital natives may offer the greatest potential for successful implementation of AI … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
(31 reference statements)
0
10
0
2
Order By: Relevance
“…Thus, we aimed to collect data on the respondent’s current awareness about AI, which is present without supplying additional external knowledge. Examinations on the consumers’ perceptions of AI in medicine are frequently carried out using online survey tools 36 , 37 or are based on analyses of social media. 38 These approaches offer a quick and simple generation of a big number of respondents, but it must not be overlooked that they are prone to methodological problems, 39 like in particular, a high risk of a selection bias excluding persons without internet access either through technical deficiencies or through missing skills.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we aimed to collect data on the respondent’s current awareness about AI, which is present without supplying additional external knowledge. Examinations on the consumers’ perceptions of AI in medicine are frequently carried out using online survey tools 36 , 37 or are based on analyses of social media. 38 These approaches offer a quick and simple generation of a big number of respondents, but it must not be overlooked that they are prone to methodological problems, 39 like in particular, a high risk of a selection bias excluding persons without internet access either through technical deficiencies or through missing skills.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that patients perceive great benefit from AI in skin cancer screening and that AI can assist dermatologists [ 30 , 43 ]. However, acceptance seems to be closely linked to the assumption that the decision-making of computer-assisted diagnostic systems is reliable, transparent, and comprehensible [ 31 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the visual diagnostic abilities of artificial intelligence and three dermatologists for skin cancer lesions, it was observed that the artificial intelligence model could better differentiate melanoma from non-melanoma, proving the model’s efficacy in discriminating pictures ( 44 ). Although AAIC is emerging in the field of skin cancer, it faces two problems: data set bias and problems in the technical application; the accepted population in translation into clinical practice is generally under the age of 35 ( 45 ). So AAIC needs more interpretability and engagement.…”
Section: Discussionmentioning
confidence: 99%